Analisis Bibliometrik Muslim Travel: Publikasi Ilmiah di Negara-Negara Seluruh Dunia - Mochammad Givary Ramadhan; M. Ruslianor Maika (Magister Tourism Study, Faculty of Tourism, Udayana University, 2022)
This study aims to determine the development map of research related to